Analisis Pemahaman Konsep Siswa Kelas IV Menggunakan Media Miniatur - Dewanti, Elsa Nigia; Erviana, Lina; Aristya, Ferry (PGSD STKIP PGRI Pacitan, 2023)
This study aims to determine: (1) learning science class IV using miniature media at SDN 2 Sidomulyo; (2) the understanding of fourth-grade students of SDN 2 Sidomulyo using miniature media in science learning. This type of research is descriptive qualitative research. The subjects of this study were selected by purposive sampling on the fourth-grade student of SDN 2 Sidomulyo. The object of this research is a miniature learning media in the fourth-grade science subject at SDN 2 Sidomulyo. Data collection techniques used are observation, interviews, documentation, and tests. The test is used to analyze student's understanding of science lessons. The validity of the data uses triangulation of sources, then data analysis uses the Miles and Huberman model which includes data reduction, data presentation, conclusions, and verification. The results of the study show that 1) the learning process using miniature media is very helpful for students in accepting the material given because they are actively involved in learning. 2) of 10 students in grade IV SDN 2 Sidomulyo have two levels of understanding, namely high (90%) and medium (10%).